A Defective Pentose Phosphate Pathway Reduces Inflammatory Macrophage Responses during Hypercholesterolemia - O'Neill, Luke; Ryan, Dylan (My University, 2018)
Metabolic reprogramming has emerged as a crucial regulator of immune cell activation, but how systemic metabolism influences immune cell metabolism and function remains to be investigated. To investigate the effect of dyslipidemia on immune cell metabolism, we performed in-depth transcriptional, metabolic, and functional characterization of macrophages isolated from hypercholesterolemic mice. Systemic metabolic changes in such mice alter cellular macrophage metabolism and attenuate inflammatory macrophage responses. In addition to diminished maximal mitochondrial respiration, hypercholesterolemia reduces the LPS-mediated induction of the pentose phosphate pathway (PPP) and the Nrf2-mediated oxidative stress response. Our observation that suppression of the PPP diminishes LPS-induced cytokine secretion supports the notion that this pathway contributes to inflammatory macrophage responses. Overall, this study reveals that systemic and cellular metabolism are strongly interconnected, together dictating macrophage phenotype and function.
PUBLISHED
cited By 0
Keywords: Immunometabolism; Inflammation; Macrophages; Hypercholesterolemia; Pentose phosphate pathway; Nrf2; Meta-inflammation; Foam cells; Atherosclerosis; Cardiovascular disease; Metabolic disease